Towards a catalogue of refactorings and code smells for AspectJ - Fernandes, João M. (2006)
In this paper, we contribute to the characterisation of a programming style specific to aspect-oriented programming. For this purpose, we present a collection of refactorings for aspect-oriented source code, comprising refactorings to enable extraction to aspects of crosscutting concerns from object-oriented legacy code, the subsequent tidying up of the extracted aspects and factoring out of common code from similar aspects to superaspects. The second group of refactorings is documented in detail. In addition, we propose some new aspect-oriented code smells, including one smell that is specific to aspect modules. We also propose a reinterpretation of some of the traditional objectoriented code smells in the light of aspect-orientation, to detect the presence of crosscutting concerns.